Pengaruh Debt to Asset Ratio dan Debt to Equity Ratio Terhadap Financial Distress yang Dimoderasi Oleh Return on Equity - Trenadhi, Raffly Pasya; Sembiring, Ferikawita Magdalena (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The purpose of this research is to explore the impact of Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) on financial distress, considering the moderating variable, return on equity (ROE). The research methodology applies panel data regression analysis and moderated regression analysis using the EViews 12 program. The research sample is obtained through purposive sampling techniques, resulting in 6 samples of publicly listed state-owned construction companies. The findings indicate that DAR has a negative impact on financial distress, DER does not significantly affect financial distress, and ROE moderates the influence of DER on financial distress. Recommendations for companies include maintaining an optimal level of debt to ensure the financial health of the company and prevent financial distress.